Body Piercings and Posttraumatic Stress Disorder Symptoms in Young Adults. (12th April 2012) - Bui, Eric; Rodgers, Rachel; Simon, Naomi M.; Jehel, Louis; Metcalf, Christina A.; Birmes, Philippe; Schmitt, Laurent
Abstract Body piercing, which is prevalent in young adults, has been suggested to be associated with features usually related to posttraumatic stress disorder (PTSD) such as high‐risk behaviours and psychopathological symptoms and might be motivated by a wish to deal with prior traumatic experiences. However, to date, no research has investigated the relationship between this practice and PTSD symptoms. The present research aims to investigate the possible relationship between body piercing and PTSD symptoms in French‐speaking young adults. According to our results, having two or more body piercings was associated with a twofold increased risk for scoring above the cut‐off score for PTSD on the PTSD checklist. Our findings suggest that two or more body piercings might serve as an identifiable marker for PTSD symptoms and may have important implications for clinical screening. Copyright © 2012 John Wiley & Sons, Ltd.